Development of allele-specific PCR based DNA test for detection of syndactylism (mule foot) related missense mutation in Holstein Friesian cattle - Anshuman Kumar,; I. D. Gupta,; Govind Mohan,; S Jayakumar,; Saket K. Niranjan, (Journal of Livestock Biodiversity, 2025)
Syndactylism or 'mule foot' is an autosomal recessive disorder of cattle, characterized by fusion of digits resulting in painful hooves and reduced mobility. The genetic defect has been reported in Holstein cattle populations, worldwide. Molecular studies have indicated the substitution of 2 nucleotides (delCGinsAT) in reading frame belonging to exon 33 of low-density lipoprotein-receptor-related protein 4 gene (LRP4) at chromosome 15 as the cause of mule foot. In this study, an allele specific polymerase chain reaction (AS-PCR) based method was developed for detecting the mule foot allele in cattle. In order to identify normal (wild-type) and mutant alleles at mule foot disease locus separately, two separate allele-specific forward primers were designed for each of the allele along with a common reverse primer. PCR reactions and conditions were standardized for amplification of each of loci separately. The wild-type and mutant alleles could be easily distinguished by detection of amplification from PCR of wild allele (CG) primer set, whereas no amplification by primer set for mutant allele (AT). Using the protocol, total 24 samples of Holstein Friesian (HF) bulls were screened, which were found to possess normal genotype at mule foot locus in all of the animals. This allelespecific PCR based DNA test was found suitable for the detection of mule foot mutation in cattle population specifically of Holstein lineages.